2006
DOI: 10.1109/tnn.2006.881485
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative Common Vector Method With Kernels

Abstract: In some pattern recognition tasks, the dimension of the sample space is larger than the number of samples in the training set. This is known as the "small sample size problem". Linear discriminant analysis (LDA) techniques cannot be applied directly to the small sample size case. The small sample size problem is also encountered when kernel approaches are used for recognition. In this paper, we attempt to answer the question of "How should one choose the optimal projection vectors for feature extraction in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 33 publications
0
70
0
3
Order By: Relevance
“…A simple Nearest Neighbour (NN) classifier is applied to the resulting KDCV feature vector. H. Cevikalp et al [4] have shown that the combination of KDCV and NN significantly outperforms several other kernel methods including KPCA+LDA and SVM in related problems.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…A simple Nearest Neighbour (NN) classifier is applied to the resulting KDCV feature vector. H. Cevikalp et al [4] have shown that the combination of KDCV and NN significantly outperforms several other kernel methods including KPCA+LDA and SVM in related problems.…”
Section: Related Workmentioning
confidence: 99%
“…This is the only point at which class label information is used during training. It is based on a kernelized variant of Linear Discriminant Analysis (LDA) [24] called KDCV [4]. Classical LDA seeks a low-dimensional projection matrix P that maximizes the objective function…”
Section: Seeking Optimal Discriminant Subspace With Kernel Trickmentioning
confidence: 99%
See 3 more Smart Citations